1969
DOI: 10.1088/0022-3727/2/2/312
|View full text |Cite
|
Sign up to set email alerts
|

The d.c. properties of an alkali plasma diode

Abstract: The theoretical d.c. current-voltage characteristics of a `collisionless' alkali plasma diode are derived. It is assumed that electrons and ions are created only at the two incandescent plane electrodes, the latter being at the same temperature. The electrons and ions are assumed to leave the electrodes with half-Maxwellian distributions of velocities. Some ions are trapped in the potential well between the electrodes. It is found that the potential distribution is associated with a double sheat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

1978
1978
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…The simultaneous excitation of high and low frequency modes in a plasma diode was also reported by Cutler & Burger (1966). Fang (1968) finds the oscillation frequency to be one third of the electron plasma frequency whereas Iannuzzi et al (1968) observed oscillations a t a frequency comparable with the plasma frequency.…”
Section: Introductionmentioning
confidence: 54%
See 3 more Smart Citations
“…The simultaneous excitation of high and low frequency modes in a plasma diode was also reported by Cutler & Burger (1966). Fang (1968) finds the oscillation frequency to be one third of the electron plasma frequency whereas Iannuzzi et al (1968) observed oscillations a t a frequency comparable with the plasma frequency.…”
Section: Introductionmentioning
confidence: 54%
“…The high frequency mode and the 'constant frequency' mode are usually observed over a similar range of applied potentials, although there are exceptions to this, as discussed later. Iannuzzi, Levine & Piperno (1968) and Fang et al (1969) and Fang (1968) have all reported observations of the high frequency mode of oscillation. The simultaneous excitation of high and low frequency modes in a plasma diode was also reported by Cutler & Burger (1966).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…9 Then the vanishing current is simply expressed by n~ = rn*, while the global electroneutrality, equivalent to </>'( -d/2) = (j)'(d/2), can be given a precise analytical form thanks to the fact that the Poisson equation happens to take the form of a pseudopotential equation 10 …”
mentioning
confidence: 99%